2012
DOI: 10.1124/dmd.112.046698
|View full text |Cite
|
Sign up to set email alerts
|

CYP2E1 Metabolism of Styrene Involves Allostery

Abstract: ABSTRACT:We are the first to report allosterism during styrene oxidation by recombinant CYP2E1 and human liver microsomes. At low styrene concentrations, oxidation is inefficient because of weak binding to CYP2E1 (K s ‫؍‬ 830 M). A second styrene molecule then binds CYP2E1 with higher affinity (K ss ‫؍‬ 110 M) and significantly improves oxidation to achieve a k cat of 6.3 nmol ⅐ min ؊1 ⅐ nmol CYP2E1 ؊1. The transition between these metabolic cycles coincides with reported styrene concentrations in blood from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 22 publications
3
44
0
1
Order By: Relevance
“…For 4-nitrophenol, metabolic rates of turnover increase and then decrease as a function of substrate concentration indicating substrate inhibition [3, 6]. Alternatively, many CYP2E1 substrates, including phenacetin, m -xylene [5], styrene [7, 8], and 7-ethoxycoumarin, demonstrate a poor efficiency in turnover at low substrate concentrations that rapidly improves at higher concentrations through a positive cooperative mechanism. Recent studies have further shown that aniline metabolism by CYP2E1 metabolism involves negative cooperativity in which higher substrate concentrations inhibit the ability for the enzyme to reach a maximal rate [9].…”
Section: Introductionmentioning
confidence: 99%
“…For 4-nitrophenol, metabolic rates of turnover increase and then decrease as a function of substrate concentration indicating substrate inhibition [3, 6]. Alternatively, many CYP2E1 substrates, including phenacetin, m -xylene [5], styrene [7, 8], and 7-ethoxycoumarin, demonstrate a poor efficiency in turnover at low substrate concentrations that rapidly improves at higher concentrations through a positive cooperative mechanism. Recent studies have further shown that aniline metabolism by CYP2E1 metabolism involves negative cooperativity in which higher substrate concentrations inhibit the ability for the enzyme to reach a maximal rate [9].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol does demonstrate the potential for combatting acrylamide induced DNA damage via Cyp2e1 inhibition. A number of other CYP2E1 inhibitors have been identified using the human enzyme and these warrant further investigation (and potential modification) to assess their ability to inhibit the effects of acrylamide [100][101][102]. Future clinical application of natural or modified CYP2E1 inhibitors may be of benefit to those males ingesting acrylamide while attempting fertilisation.…”
Section: Inhibiting Acrylamide's Toxic Effectsmentioning
confidence: 99%
“…2 Kinetic profiles for CYP2E1 substrates are often hyperbolic and thus best fit to the Michaelis-Menten equation in which the metabolic efficiency is constant. Unlike traditional enzymes, a more complex array of mechanistic possibilities are possible for CYP2E1 based on recent steady-state studies on toxicologically important substrates including aniline, 3 styrene, 4 and m -xylene. 5 The metabolism of those pollutants involved non-hyperbolic kinetic profiles, whereby metabolic efficiency either increased (positive cooperativity) or decreased (negative cooperativity or substrate inhibition) as a function of substrate concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Those kinetic profiles could be explained through mechanisms involving catalytic and effector sites for CYP2E1. 3, 4, 611 Their presence and specificities were further characterized through experimental catalytic inhibition 6, 8, 12 and binding 6, 8 studies and computational docking and Molecular Dynamics simulations 11 using a series of mono- and bi-cyclic azoles. A hallmark of these studies has been the capacity of substrates alone and combined with inhibitors to impact CYP2E1 metabolic efficiency in ways unexpected by the traditional Michaelis-Menten mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation